EFEKTIVITAS PENGGUNAAN MEDIA POWERPOINT INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Peransisca Hasibuan, Lidiya; Gusnardi; Hendripides (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low motivation of students to learn, especially in the subject of Creative Products and Entrepreneurship caused by the use of conventional learning media. This study aims to test the effectiveness of the use of interactive PowerPoint media in increasing students' learning motivation. The method used is a quantitative approach with a quasi-experimental design through a pretest-posttest control group design pattern. The research population amounted to 130 students, with a sample of 54 students and was selected using the class-based Cluster Sampling technique (intact group). The determination of this sample also contains elements of Purposive sampling. The results on the paired sample t-test of the control and experimental classes showed a significance value of 0.000 < 0.05. In addition, the results of the independent sample t-test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05. The average N-Gain value of the control class was 16.97% (low category), while the experimental class was 57.80% (medium category). This shows that the use of interactive PowerPoint media is more effective in increasing students' learning motivation compared to conventional methods. Thus, interactive PowerPoint media can be recommended as an innovative learnig alternative to increase students' motivation to learn.